Outcome of Left Lobe Living-Donor Liver Transplantation in Tokushima. (July 2018) - Imura, Satoru; Teraoku, Hiroki; Saito, Yu; Iwahashi, Shuichi; Ikemoto, Tetsuya; Morine, Yuji; Shimada, Mitsuo
Abstract : Introduction: There is the risk of small-for-size graft (SFSG) in left lobe living-donor liver transplantation (LL-LDLT) for adult patients. However, to minimize donor's risk, LL-LDLT might be an ideal option in adult-to-adult LDLT. The aim of the study was to assess the outcome and feasibility of adult-to-adult LL-LDLT in our hospital. Patients: Between 2005 and 2017, twenty-four consecutive LDLTs were performed at Tokushima University Hospital. Of the 24 adults, 21 patients underwent LDLT using LL-grafts with (n=16) or without (n=5) the caudate lobe. Four of 7 patients with HCC had HCC beyond the Milan criteria. Four cases with ABO-incompatible LDLT were included. Results: The mean graft weight of LL-grafts was 440g (340-520g), GV/SLV and GRWR were 39.1% (29.3-50.8%) and 0.77% (0.55-1.13). SFSG, defined as graft volume-to-recipient standard liver volume (GV/SLV) <40% or graft-to recipient weight ratio (GRWR) <0.8, was identified in 13 cases. Postoperative complications were dissection of hepatic artery (n=1), sepsis (n=1), hemophagocytic syndrome (n=1), small-for-size syndrome (n=1), hemorrhage (n=3), refractory CMV infection (n=1), severe pneumonia (n=1). No significant difference was observed in the incidence of postoperative complications between the SFSG group and non SFSG group. The overall 1-, 3-, 5- and 10-year patient survival rates in LL-LDLT were 95%, 90%, 90% and 84%, respectively. Two HCC patients were lost due to recurrence. There was no significant difference in patient survival between the SFSG group and non SFSG group. Four cases with ABO-incompatible LDLT are all alive without antibody mediated acute rejection. Conclusion: Adult-to-adult LL-LDLT, even if SFSG was used, was found to be feasible without affecting patient survival. Utilization of LL-grafts should be undertaken to keep the chance of donor morbidity and mortality minimal.